PEMANTAPAN HUKUM DALAM SISTEM PERADILAN - Sri Wulandari Sri Wulandari (FEB UNTAG Semarang, 2012)
Abstract In the development of the law of a country that wants to have an authoritative legal system should try to make its justice system to be